The Experience of Muslim Students in the Catholic Academia - Velez, Don Antonio; Camilo, Taaliah Hajra (TARBIYA: Journal of Education in Muslim Society, 2024)
AbstractThis study investigates Muslim students' experiences at a Catholic university in Mindanao, including their perceptions of institutional support for religious practice and identity construction. A quantitative approach was utilized to gather data via an online survey, employing a snowball sampling technique, which involved 60 Muslim students from diverse academic programs participating in the study. The study assesses satisfaction levels across three primary domains: classroom instruction, co-curricular activities, and extracurricular engagement. The results demonstrate that Muslim students typically report a strong sense of satisfaction regarding their classroom instruction and participation in co-curricular activities. Nonetheless, participation in extracurricular activities garnered lower satisfaction scores, underscoring a disparity between the institution's dedication to inclusivity and the actual experiences of students in more informal social environments. This discrepancy indicates a necessity for focused institutional initiatives aimed at improving inclusion outside of academic environments, especially in extracurricular activities where informal interactions significantly influence student experiences. The findings enhance the discourse surrounding religious pluralism in higher education, highlighting the necessity for organized support systems that reach beyond just academic and co-curricular environments. By enhancing its dedication to inclusive extracurricular programs, the university can cultivate a more comprehensive and fair learning atmosphere. Finally, while the university has demonstrated strengths in promoting religious inclusiveness, resolving extracurricular concerns is critical to ensuring that students from all faith backgrounds feel appreciated and involved.. Abstrakpenelitian ini menyelidiki pengalaman mahasiswa Muslim di sebuah universitas Katolik di Mindanao, termasuk persepsi mereka terhadap dukungan institusional terhadap praktik keagamaan dan pembentukan identitas. Pendekatan kuantitatif digunakan untuk mengumpulkan data melalui survei daring dengan teknik snowball sampling, yang melibatkan 60 mahasiswa Muslim dari berbagai program akademik dalam penelitian ini. Studi ini menilai tingkat kepuasan dalam tiga domain utama: pembelajaran di kelas, kegiatan ko-kurikuler, dan keterlibatan dalam kegiatan ekstra-kurikuler.Hasil penelitian menunjukkan bahwa mahasiswa Muslim umumnya melaporkan tingkat kepuasan yang tinggi terhadap pengalaman mereka dalam pembelajaran di kelas dan partisipasi dalam kegiatan ko-kurikuler. Namun, keterlibatan dalam kegiatan ekstra-kurikuler memperoleh skor kepuasan yang lebih rendah, menyoroti adanya kesenjangan antara komitmen institusi terhadap inklusivitas dan pengalaman nyata mahasiswa dalam lingkungan sosial yang lebih informal. Disparitas ini mengindikasikan perlunya inisiatif kelembagaan yang lebih terarah untuk meningkatkan inklusi di luar lingkungan akademik, terutama dalam kegiatan ekstra-kurikuler di mana interaksi informal memiliki pengaruh signifikan terhadap pengalaman mahasiswa.Temuan ini memperkaya diskusi mengenai pluralisme agama dalam pendidikan tinggi, dengan menekankan pentingnya sistem dukungan yang terstruktur dan mencakup lebih dari sekadar lingkungan akademik dan ko-kurikuler. Dengan meningkatkan komitmennya terhadap program ekstra-kurikuler yang inklusif, universitas dapat menciptakan suasana belajar yang lebih komprehensif dan adil. Pada akhirnya, meskipun universitas telah menunjukkan keunggulan dalam mempromosikan inklusivitas keagamaan, penyelesaian tantangan dalam aspek ekstra-kurikuler sangat penting untuk memastikan bahwa mahasiswa dari semua latar belakang keagamaan merasa dihargai dan terlibat sepenuhnya.How to Cite: Velez, D.A., & Camilo, T.H. (2024). The Experience of Muslim Students in the Catholic Academia. TARBIYA: Journal of Education in Muslim Society, 11(2), 225-238. https://doi.org/10.15408/tjems.v11i2.42663